A network pharmacology approach to investigate the blood enriching mechanism of Danggui buxue Decoction. (10th May 2019) - Shi, Xu-Qin; Yue, Shi-Jun; Tang, Yu-Ping; Chen, Yan-Yan; Zhou, Gui-Sheng; Zhang, Jing; Zhu, Zhen-Hua; Liu, Pei; Duan, Jin-Ao
Abstract: Ethnopharmacological relevance: Danggui buxue Decoction (DBD) has been frequently used to treat with blood deficiency, which consisted of Danggui (DG) and Huangqi (HQ) at a ratio of 1:5. Accumulating evidence showed that blood deficiency in traditional Chinese medicine (TCM) was similar to anemia in modern medicine. Aim of the study: The purpose of this study was to explore its therapeutic mechanism of with network pharmacology approach. Materials and methods: We explored the chemical compounds of DBD and used compound ADME screening to identify the potential compounds. Targets for the therapeutic actions of DBD were obtained from the PharmMapper, Swiss, SEA and STITCH. GO analysis and pathway enrichment analysis was performed using the DAVID webserver. Cytoscape was used to visualize the compound-target-pathway network for DBD. The pharmacodynamics and crucial targets were also validated. Results: Thirty-six potential active components in DBD and 49 targets which the active components acted on were identified. 47 KEGG pathways which DBD acted on were also come to light. And then, according to KEGG pathway annotation analysis, only 16 pathways seemed to be related to the blood nourishing effect of DBD, such as PI3K-AKT pathway, and so on. Only 32 targets participated in these 16 pathways and they were acted on by 29 of the 36 active compounds. Whole pharmacodynamic experiments showed that DBD had significant effects to blood loss rats. Furthermore, DBD could promote the up-regulation of hematopoietic and immune related targets and the down-regulation of inflammatory related targets. Significantly, with the results of effective rate, molecular docking and experimental validation, we predicted astragaloside IV in HQ, senkyunolide A and senkyunolide K in DG might be the major contributing compounds to DBD's blood enriching effect. Conclusion: In this study, a systematical network pharmacology approach was built. Our results provided a basis for the future study of senkyunolide A and senkyunolide K as the blood enriching compounds in DBD. Furthermore, combined network pharmacology with validation experimental results, the nourishing blood effect of DBD might be manifested by the dual mechanism of enhancing immunity and promoting hematopoiesis. Graphical abstract: fx1